2000
DOI: 10.1289/ehp.001081171
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of nonsmoking women exposed to spouses who smoke: epidemiologic study on environment and health in women from four Italian areas.

Abstract: The aim of this study was to evaluate whether risk factors associated with cardiovascular or respiratory diseases and lung cancer occur differently among nonsmoking women in Italy with and without exposure to environmental tobacco smoke (ETS) from husbands that smoke. We performed a cross-sectional study of 1,938 nonsmoking women in four areas of Italy. Data on respiratory and cardiovascular risk factors and on diet were collected using self-administered questionnaires. Medical examinations and blood tests wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 32 publications
1
25
1
Order By: Relevance
“…As a single factor, there are limited reports on the influence of the lowprotein diet in conjunction with the tobacco smoke exposure. 11 In the present study, we found that MI and FecI decreased with the increasing concentration of tobacco smoke. The changes of MI were not augmented by the low-protein diet, as they were for FecI.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…As a single factor, there are limited reports on the influence of the lowprotein diet in conjunction with the tobacco smoke exposure. 11 In the present study, we found that MI and FecI decreased with the increasing concentration of tobacco smoke. The changes of MI were not augmented by the low-protein diet, as they were for FecI.…”
Section: Discussionsupporting
confidence: 60%
“…As it was shown in previous publications, the tobacco smoking habit may coexist with the lower socioeconomic status, and as such correlated with improper diet 2,11 For the developing fetus, particularly important are the deficits of proteins, which may lead not only to delays in growth but can also influence toxicity of various compounds. However, there are reports on the influence of tobacco smoke exposure on the developing fetuses and on the growth of newborns.…”
Section: Discussionmentioning
confidence: 92%
“…We noted that women with lower levels of education had a higher probability of exposure to ETS [17].…”
Section: Discussionmentioning
confidence: 66%
“…We noted that women with lower levels of education had a higher probability of exposure to ETS [21]. …”
Section: Discussionmentioning
confidence: 99%